Recurrent leukoencephalopathy with microhemorrhages: gradient-echo MRI study diagnostic value in CNS primary angiitis - Arias, M; Osorio, XR; Dapena, D; Arias-Rivas, S; Vázquez, F (Multiple sclerosis, 2008)
Diagnosis of primary angiitis of the central nervous system (PACNS) is difficult in relation to variability in its clinical manifestations and absence of specific signs in neuroimaging. A young patient presented with a recurrent encephalopathic clinical course. T2 and fluid-attenuated inversion recovery-magnetic resonance imaging (FLAIR-MRI) showed hyperintense lesions in the cerebral white matter suggesting demyelination. Those lesions decreased or even disappeared after treatment with steroids and immunoglobulins. In echo gradient MRI (T2*-MRI), there were permanent cortical-subcortical petechial hypointense lesions (microhemorrhages). Definite diagnosis was established after cerebral biopsy. Intravenous cyclophosphamide was administrated with no new relapses in more than 18 months of follow-up. In a compatible clinical course, the finding of petechial hemorrhages in T2*-WI could play an important role in early diagnosis of PACNS.